2020
DOI: 10.1111/1467-8489.12395
|View full text |Cite
|
Sign up to set email alerts
|

Farm machinery use and maize yields in China: an analysis accounting for selection bias and heterogeneity

Abstract: Crop production in developing and emerging countries is increasingly dependent on the usage of farm machinery. However, it remains unclear whether low-productive and high-productive farmers benefit equally from farm machinery use. To address the research gap, this study examines the potential heterogeneous effects of farm machinery use on maize yields, using an unconditional quantile regression model and survey data from China. We employ a control function approach to address the selection bias issue associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 61 publications
4
30
0
Order By: Relevance
“…We use Cochran’s formula to determine the sample size due to a lack of information on the population of wheat farmers in the survey regions (Cochran, 1977; Zhou et al ., 2020). Cochran’s formula is expressed as n0=pqZ2/e2, where we assume a P ‐value of 0.5, a confidence level q of 95%, a Z ‐value of 1.96 and margin of error e of 5%.…”
Section: Data Variables and Descriptive Statisticsmentioning
confidence: 99%
“…We use Cochran’s formula to determine the sample size due to a lack of information on the population of wheat farmers in the survey regions (Cochran, 1977; Zhou et al ., 2020). Cochran’s formula is expressed as n0=pqZ2/e2, where we assume a P ‐value of 0.5, a confidence level q of 95%, a Z ‐value of 1.96 and margin of error e of 5%.…”
Section: Data Variables and Descriptive Statisticsmentioning
confidence: 99%
“…Another limitation in previous marginal land studies is the lack of understanding about the drivers of farmers' heterogeneous perceptions of marginal land availability. Numerous studies have demonstrated the existence of heterogeneous behavior rules in farmers' land‐use decisions (Fewell et al, 2016; Garrod et al, 2012; Zhou et al, 2020). However, little is known about the heterogeneity of farmers' perceptions on marginal land availability, especially how the dominant causes of land marginality vary among farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have analyzed the factors influencing the adoption of agricultural machinery by Chinese maize farmers [4,[7][8][9][10][11] (Table 1). These factors mainly include three aspects: farmer features (e.g., age, gender, education level, farming experience, off-farm employment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…"+" means a positive effect and "−" means a negative effect. Specifically, Zhou et al [11] estimated the impacts of farm machinery use on maize yields by using a control function approach. In the first stage, smartphone use was employed as an instrumental variable in the farm machinery adoption equation; in the second stage, the inverse mills ratio estimated from the first stage was added to the maize production function as an extra regressor to correct the endogeneity issue caused by selection bias in farm machinery adoption.…”
Section: Introductionmentioning
confidence: 99%